FAKTOR-FAKTOR YANG MEMPENGARUHI KINERJA GURU: KOMPENSASI, MOTIVASI KERJA DAN LINGKUNGAN KERJA DI MI MIFTAHUL HUDA TEGALSAMBI TAHUNAN JEPARA - Rohmah; Sukarman; Nurmala Fadhilah Jaya (STKIP Subang, 2025)
This study aims to analyze the factors that influence teacher performance, namelycompensation, work motivation, and work environment at MI Miftahul HudaTegalsambi Tahunan Jepara. Teacher performance is a key factor in the successof education, so it is important to understand the aspects that support it. Thisresearch uses a qualitative approach of case study type with data collectiontechniques through observation, interviews, and documentation. The results showthat adequate compensation, high levels of work motivation and a conducive workenvironment have a positive influence on improving teacher performance. Thefindings provide strategic recommendations for policy makers and schoolmanagement in an effort to improve the quality of education in a sustainablemanner.